Proceedings of the 16th International Conference on Human-Computer Interaction With Mobile Devices &Amp; Services 2014
DOI: 10.1145/2628363.2628368
|View full text |Cite
|
Sign up to set email alerts
|

Cuenesics

Abstract: Figure 1. People performing mid-air gestures to select items on interactive public displays. The system was installed at three locations: (L1) on a large wall-projection in a coworking space, (L2) on a rear-projection screen in a students' cafeteria, (L3) on an LCD at a venue's opening event ABSTRACTMost of today's public displays only show predefined contents that passers-by are not able to change. We argue that interactive public displays would benefit from immediately usable mid-air techniques for choosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Among them, touchless gestural interaction limits vandalism by placing displays in unreachable places [31], keeping a high hygiene level of the screen surface [19], and removing constraints to the display size (see, for instance, works on media façades [9]). Walter et al [34] focused their work on describing existing solutions found in literature, for user representation in touchless gestural applications. Recently, other works focused on the use of silhouettes or avatars [18,23], since they have proved to be very effective in solving some common pervasive display issues, namely interaction blindness (i.e.…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, touchless gestural interaction limits vandalism by placing displays in unreachable places [31], keeping a high hygiene level of the screen surface [19], and removing constraints to the display size (see, for instance, works on media façades [9]). Walter et al [34] focused their work on describing existing solutions found in literature, for user representation in touchless gestural applications. Recently, other works focused on the use of silhouettes or avatars [18,23], since they have proved to be very effective in solving some common pervasive display issues, namely interaction blindness (i.e.…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 99%
“…Indeed, an appropriate interface could strongly contribute to address both the interaction blindness and affordance blindness and could make the interaction itself more intuitive and straightforward. Many prior works suggested the use of avatar-based interfaces, where a predominant human-shaped entity continuously reproduces user movements [18,23,33,34]. These studies revealed the effectiveness of silhouettes, mirror images or avatars in communicating the supported interactivity and its touchless nature.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work investigated different ways of representing users on public displays: Appearance matching representations include silhouettes [2] (aka contours [31,34]) and mirrors [26] ( Figures 1C and 1D). Kinestheticvisual matching ones include abstract objects [19,35,37], avatars [26], and skeletons [2,35,36] ( Figures 1A and 1B).…”
Section: User Representationsmentioning
confidence: 99%
“…The past years witnessed an extensive employment of user representations on the display. These representations can serve multiple purposes; previous work employed them to attract the attention of passersby [26,36], initiate interaction with the display [35], and provide real-time feedback to users [1]. In most of these works, multi-user interaction is supported by showing multiple on-screen representations simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating the use of both speech and gesture in computer understanding has been an ongoing challenge since the introduction of the point and manipulate "Putthat-there" system by Bolt [1]. A large amount of work has focused on designing and developing gesture-based interaction systems ranging from mobile systems [2,9,10] to large-screen displays [14,19,20], as well as researching the relationships used in multimodal and gestural interaction [6][7][8]12,[15][16][17][18].…”
Section: Related Workmentioning
confidence: 99%